The role of satisfaction as a mediating variable on the effects of novelty seeking and familiarity on tourist revisit intention - Regina Priya Agustina; Yessy Artanti (Diponegoro International Journal of Business, 2020)
The development of tourism is important for people's lives because it is related to impact on economic, social, cultural and educational developments both nationally and internationally. Therefore, businessman in the tourism sector are expected to be able to maintain good relations with tourists who visit in order to have the revisit intention in the future. The purpose of this study was to analyze and discuss the novelty seeking and familiarity on revisit intention with satisfaction as mediating variable in the city of Surabaya. Data collection method is done by online questionnaire. The sampling technique of this study was nonprobability sampling with judgmental sampling method. Respondents used were 200 respondents who had visited artificial tourist destinations in the city of Surabaya in the last 2 years. Analysis of the data used is path analysis. The results showed that novelty seeking had no significant effect on revisit intention, while familiarity and satisfaction had a significant effect on revisit intention. Likewise, both novelty seeking and familiarity significantly influence satisfaction.